This Time Is the Same: Using Bank Performance in 1998 to Explain Bank Performance during the Recent Financial Crisis - FAHLENBRACH, RÜDIGER; PRILMEIER, ROBERT; STULZ, RENÉ M. (Journal of Finance, 2012)
ABSTRACT Are some banks prone to perform poorly during crises? If yes, why? In this paper, we show that a bank's stock return performance during the 1998 crisis predicts its stock return performance and probability of failure during the recent financial crisis. This effect is economically large. Our findings are consistent with persistence in a bank's risk culture and/or aspects of its business model that make its performance sensitive to crises. Banks that relied more on short‐term funding, had more leverage, and grew more are more likely to be banks that performed poorly in both crises.